2019
DOI: 10.1155/2019/5363261
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Colorectal Cancer in Ulcerative Colitis Patients: A Systematic Review and Meta-Analysis

Abstract: Background Ulcerative colitis (UC) patients have an increased risk for the development of colorectal cancer (CRC). Our aim was to assess the risk of CRC in UC patients compared with disease extent, disease duration, and geographic variation. Methods In this systematic review and meta-analysis, we searched PubMed, scientific meetings, and the bibliographies of identified articles, with English language restrictions for studies published from 1988 to 2018, and assessed the risk of CRC in UC patients. Patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(44 citation statements)
references
References 68 publications
2
40
1
1
Order By: Relevance
“…Inflammatory bowel diseases (IBD) including Crohn's disease (CD) and ulcerative colitis (UC) are complex chronic inflammatory disorders of unknown origin that could affect the intestinal tract (77). Colitis-associated cancer (CAC) may develop in patients with IBD, which is primarily due to chronic intestinal inflammation (78,79). It is reported that the cumulative incidence of CRC by colitis duration was 2.5% at 20 years, 7.6% at 30 years, and 10.8% at 40 years (78).…”
Section: Functions Of γδ T Cells In Ibd and Cacmentioning
confidence: 99%
“…Inflammatory bowel diseases (IBD) including Crohn's disease (CD) and ulcerative colitis (UC) are complex chronic inflammatory disorders of unknown origin that could affect the intestinal tract (77). Colitis-associated cancer (CAC) may develop in patients with IBD, which is primarily due to chronic intestinal inflammation (78,79). It is reported that the cumulative incidence of CRC by colitis duration was 2.5% at 20 years, 7.6% at 30 years, and 10.8% at 40 years (78).…”
Section: Functions Of γδ T Cells In Ibd and Cacmentioning
confidence: 99%
“…The connection between inflammation and malignant diseases has been well-established based on evidence from epidemiological, genetic, or pharmacological studies. In the case of colon malignancies, IBDs especially ulcerative colitis and Crohn's disease exhibit consistent association with an elevated risk of CRC (Choi et al, 2019;Zhou et al, 2019;Oleń et al, 2020). IBDassociated CRC is characterized by early onset (Keller et al, 2019), increased formation of synchronous, and poorly differentiated tumors (Reynolds et al, 2017) as well as elevated mortality rate (Sebastian et al, 2014), in relation to sporadic CRC.…”
Section: The Underlying Molecular Mechanisms Of Colon Carcinogenesis mentioning
confidence: 99%
“… 35 , 36 Moreover, as a consequence of chronic intestinal inflammation, patients with IBD are two to sixfold more likely to develop colorectal cancer than the general population. 37 , 38 Colorectal cancer is the third most common type of cancer and the fourth cancer-related cause of death worldwide, with over 1.2 million new cases and 900,000 deaths per year, with a growing incidence in developing countries. 39 The cell of origin for most colorectal cancers is thought to be a stem cell.…”
Section: Function Cell Biology and Physiopathology Of The Intestinementioning
confidence: 99%